Derivative of polynomials and exponentials

Derivative of polynomials and exponentials - h e h-1 h = 1....

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
DERIVATIVES OF POLYNOMIALS AND EXPONENTIAL FUNCTIONS For basic functions, we have differentiation rules as follows. 1. d dx ( c ) = 0. 2. d dx ( x ) = 1. 3. d dx ( x n ) = nx n - 1 . If we know derivatives of certain functions, we can calculate derivatives of new functions by using old ones. 4. d dx [ cf ( x )] = cf 0 ( x ). 5. d dx [ f ( x ) + g ( x )] = f 0 ( x ) + g 0 ( x ). 6. d dx [ f ( x ) - g ( x )] = f 0 ( x ) - g 0 ( x ). By using above rules, we can differentiate any polynomials. Example 1. Find The derivative of the function f ( x ) = 2 x 2 + 4 x + 1. Solution f 0 ( x ) = d dx (2 x 2 + 4 x + 1) = 2 d dx ( x 2 ) + 4 d dx ( x ) + d dx (1) = 2(2 x ) + 4(1) + 0 = 4 x + 4 Example 2. Find The derivative of the function f ( x ) = a x . Solution f 0 ( x ) = lim h 0 f ( x + h ) - f ( x ) h = lim h 0 a x + h - a x h = lim h 0 a x ( a h - 1) h = a x lim h 0 a h - 1 h In the example above, we do not know the limit lim h 0 a h - 1 h . However, if the limit is 1, then we can get a function whose derivative equals itself. Because this type of function is frequently used, we define a number a with this property as follows. Definition 1. e is the number such that lim
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: h e h-1 h = 1. 1 2 DERIVATIVES OF POLYNOMIALS AND EXPONENTIAL FUNCTIONS From the denition, we can get the following dierentiation formula. Theorem 1. d dx ( e x ) = e x Example 3. If f ( x ) = e x-x 2 + 3 x , nd f and f 00 . Solution f ( x ) = d dx ( e x-x 2 + 3 x ) = d dx ( e x )-d dx ( x 2 ) + 3 d dx ( x ) = e x-2 x + 3 f ( x ) = d dx ( e x-2 x + 3) = d dx ( e x )-2 d dx ( x ) + d dx (3) = e x-2 Example 4. Find an equation of the normal line to the curve y = e x-x 2 + 3 x at the point P (0 , 1). Solution Since the slope of the tangent line at the point P is y (0) = 4, we can see that the slope of the normal line is-1 4 . Thus, the equation of the normal line is y-1 =-1 4 ( x-0) , or y =-1 4 x + 1 ....
View Full Document

Page1 / 2

Derivative of polynomials and exponentials - h e h-1 h = 1....

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online